2019
DOI: 10.1002/berj.3544
|View full text |Cite
|
Sign up to set email alerts
|

Using research to promote equity within education systems: Possibilities and barriers

Abstract: This article provides an evaluative account of its authors’ involvement in three major national improvement initiatives. Set in the context of three of the countries that make up the UK, these developments were focused in particular on the promotion of educational equity. Unusually, the analysis provided compares evidence collected from an insider perspective with data generated through independent evaluations. In so doing, it considers how research and researchers can contribute to system change by using rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 22 publications
0
12
0
4
Order By: Relevance
“…More broadly, Chapman and Ainscow (2019), drawing on their experiences of using research to change education systems, including the role that collaboration plays in this process, identify three factors that can hinder organisational partnership activity (including collaboration between schools). These are social factors (including pre‐existing relationships between partners that encourage mutual support), political factors (attitudes and priorities of key partners) and cultural factors (local traditions and expectations of partners as to what is possible).…”
Section: Resultsmentioning
confidence: 99%
“…More broadly, Chapman and Ainscow (2019), drawing on their experiences of using research to change education systems, including the role that collaboration plays in this process, identify three factors that can hinder organisational partnership activity (including collaboration between schools). These are social factors (including pre‐existing relationships between partners that encourage mutual support), political factors (attitudes and priorities of key partners) and cultural factors (local traditions and expectations of partners as to what is possible).…”
Section: Resultsmentioning
confidence: 99%
“…We believe that our review is an example of Chapman and Ainscow's (2019) call for research that promotes equity, social learning, and local knowledge creation within specific settings. Through this review, it may be concluded that CLIL in Latin America has adopted a broader pedagogical perspective; nonetheless, we observed a tendency for CLIL research to be carried out through action research or mixed methods usually by teacher researchers focused on their own practices.…”
Section: Discussionmentioning
confidence: 99%
“…Todas estas investigaciones parecen indicar que pertenecer a un grupo de FPP en el que se realice I-A refuerza la función investigadora del docente. Además, refuerza la reflexión crítica, las prácticas educativas transparentes, igualitarias y equitativas que fomenten la inclusión, así como favorece la mejora de la calidad del proceso de enseñanza-aprendizaje (López et al 2016); trabajar en grupo afianza el aprendizaje colaborativo que se produce entre docentes y permite superar el aislamiento profesional (Chapman & Ainscow, 2019;Walton & Sutherland, 2020).…”
Section: Formación Permanente Colaborativa Del Profesorado a Través D...unclassified